Let's solve your equation step-by-step.
(− 1 /5 )(c)+2+c= 1 /5 (10c−20)
Step 1: Simplify both sides of the equation.
(− 1 /5 )(c)+2+c= 1 /5 (10c−20)
(− 1 /5 )(c)+2+c=( 1 /5 )(10c)+( 1 /5 )(−20) (Distribute)
−1 /5 c+2+c=2c+−4
( −1 /5 c+c)+(2)=2c−4 (Combine Like Terms)
4 /5 c+2=2c−4
4 /5 c+2=2c−4
Step 2: Subtract 2c from both sides.
4/5 c+2−2c=2c−4−2c
−6 /5 c+2=−4
Step 3: Subtract 2 from both sides.
−6 /5 c+2−2=−4−2
−6 /5 c=−6
Step 4: Multiply both sides by 5/(-6).
( 5 /−6 )*( −6 /5 c)=( 5 /−6 )*(−6)
c=5
Answer:
c=5